Germ Tube Induction Test Comparing Total of Six Liquid and Three Solid Media in Candida albicans - Ruby, Rivaldi; Arifin, Erlangga Saputra; Kurniawan, Sandy Vitria; Surja, Sem Samuel (Indonesian Journal of Tropical and Infectious Disease, 2023)
Invasive candidiasis (IC) has a high mortality rate of 70%, thus diagnosis should be established without delay. Given its fast result, serological test such as β-d-glucan (BDG) test is one alternative diagnosis modalities. However, it lacks specificity. Candida albicans germ tube antibody (CAGTA) test is an alternative serological test which has a high sensitivity of 76.2% and specificity of 80.3%.  Manufacturing CAGTA serological test requires provision of specific germ tube antigen. In this study, various culture media were tested to find the best media for germ tube induction. This study was an experimental in vitro study. The number and length of the germ tube were recorded in two- and three-hour incubation periods. A total of six samples containing one C. albicans ATCC 90028, four C. albicans wild type strains, and one C. krusei wild type strain were used. Nine media were tested to induce germ   tube formation: human and sheep serum, fetal bovine serum, mueller hinton agar and broth, tryptic soy agar and broth, brain heart infusion agar and broth. At both incubation periods, the medium with the highest number of germ tube was human serum (p=0.001 and p=0). The longest germ tube was found in sheep serum at two-hour incubation period (p=0.005). Mueller hinton broth (MHB) showed comparable results with human and sheep serum (p>0.05). Human serum is a superior inducer of morphogenesis. However, the use of MHB is recommended in this study, since provision of fresh human and sheep serum on a regular basis is impractical.